Pagastia (P.) donoliveri sp. nov.—a new Nearctic alpine stream chironomid species (Diptera: Chironomidae: Diamesinae) from the Beartooth Mountains, Wyoming, U.S.A. - Makarchenko, Eugenyi A.; Hansen, Dean C. (Zootaxa, 2020)
An illustrated description of the adult male of Pagastia (P.) donoliveri sp. nov. from the Beartooth Mountains, Wyoming, of North America is provided. An updated key to the determination of all known Holarctic species of Pagastia Oliver for males is also provided.